Income-Health Expenses and Use of Medicinal Plants by Tribal Communities in Panch Mahal District of Gujarat - Jat, R. S.; Bansal, Ruchi; Jadav, J. K.; Kumar, Raj (Indian Forester, 2016)
A semi-structured ethnomedicinal survey from Godhra region in Panch Mahal district of Gujarat was conducted during 2013-14 to gather information from the tribal community elders. During the survey, 50 tribal farmers were interviewed for socio-economic and ethnomedicinal informations like; income, land holding, expenditure on medicines, use of medicinal plants for ailments and diseases, and use methods. Results showed that majority of the farmers were marginal and spending 12-17% of their income on healthcare facilities. In this region, most frequently occurring diseases were cold and fever, and mostly treated with medicinal plants available in the periphery. The highest informants consensus factor (ICF) value (1.0) for the use of medicinal plants was reported for jaundice, gastric problems, tooth problem and wounds. Among medicinal plants, Ocimum sanctum and Azadirachta indica have great use in the treatment of common diseases and recorded maximum citations. Ocimum sanctum recorded highest use value of 0.94 for the treatment of fever, cough and cold, followed by Azadirachta indica with use value of 0.92 for the treatment of fever and tooth problems were playing significant role in traditional medicines. The most common method of use of medicinal plants was either decoction or leaf extract or juice of the plant.